Survival Model Estimator for Type II Censored Data Based on Lognormal Distribution - Eduardus Beo Seso Delvion; Cecilia Novianti Salsinha; Minanur Rohman (RANGE: Jurnal Pendidikan Matematika, 2024)
The problems that occur in analyzing survival models based on parametric distributions require parameter values ​​obtained from estimators. This study aims to obtain an estimator model of the lognormal distribution which has parameters and . Therefore, the maximum likelihood method approach is used to obtain the estimators and . However, the problem encountered is that the maximum likelihood model of the lognormal distribution for Type II cencoring data produces quite complex equations, so an approach with a Taylor series is needed only for the first order. The results obtained are estimators and which can be applied to Type II cencoring data based on a lognormal distribution.